SELEKSI INDIVIDU PADA POPULASI KACANG BOGOR (Vigna subterranea L. Verdc.) ASAL SUKABUMI DAN SUMEDANG DI LAHAN ULTISOL JAMBI - Jeremia Manurung; Sosiawan Nusifera; Buhaira; Theodora; Ria Rif'atunidaudina (JURNAL AGROTROPIKA, 2026)
Bogor bean (Vigna subterranea (L.) Verdc.) are plants that have many advantages. Bogor beans are easy to cultivate because they are tolerant to water and nutrient limitations. Bogor beans have good nutritional content, namely high carbohydrate and protein and relatively low fat, so they can be used as an alternative food source. In addition, Bogor beans can also be used as an alternative crop for dry land cultivation. This study aims to select superior individuals from the Bogor bean populations originating from Sukabumi and Sumedang and to determine the closeness of the relationship between two variables in the Bogor bean populations originating from Sukabumi and Sumedang. This study used an experimental method without a specific environmental design and was designed by dividing the planting plots into two large plots differentiated by population origin. The characteristics observed included the number of leaves, canopy width, plant height, fresh pod weight, dry pod weight, number of pods per plant, number of filled pods, number of empty pods, fresh pod weight, pod length and width, seed length and width, and weight of 100 seeds. This study was conducted at the Teaching and Research Farm of the Faculty of Agriculture, University of Jambi, Unja Mendalo Campus, Jambi Luar Kota District, Muaro Jambi Regency from September 2024 to March 2025. The data obtained were analyzed using the coefficient of variation, mean value, t-test, differential selection, and correlation. The results show that of the 10 superior individuals selected from the original population in Sukabumi, they include A1, A2, A11, A31, A37, A46, A52, A57, A81, A82, while in the Sumedang population they included B6, B21, B35, B39, B44, B55, B56, B64, B68, B77. The Sukabumi population, when compared to the Sumedang population, has superior characteristics based on the variables of fresh pod weight, dry pod weight, number of pods per plant, and number of mature pods. Meanwhile, the Sumedang population, when compared to the Sukabumi population, has superior characteristics based on the variables of fresh pod weight, pod length, seed length, and weight of 100 seeds.